EFEKTIVITAS PENGGUNAAN METODE DEMONSTRASI BERBASIS PREDICT- OBSERVE- EXPLAIN PADA MATERI PEMANASAN GLOBAL - Siswi, Nur Rokhmani Tri (2015)
Learning by using demonstration methods based Predict- Observe- Explain (POE) on the matter of global warming showed good results. The ability of the students about the prediction, observation, and explanations can be developed using this method. The level of effectiveness of learning activities students are very good at the level 1 of effectiveness. Development toward level 2 can be done with the effectiveness of capacity-prediction and explanation. Indicators are achieved according to the expected amount to two indicators of the five indicators set. Increase in the average pretest-posttest students showed an increase of 6.47 points, although the index Gain still gained of 0.3. The percentage of student engagement in learning activities with demonstrations method based POE reached an average of 92%. This means that students undertake planned activities in the learning process well. The ability of students in terms of observation is very visible and very prominent, followed by the ability of prediction and explanation by percentage based spreadsheet of students by 83.3% to powers of observation, 80% for prediction capabilities, and 70% for the ability of explanation. Correspondence between planning and implementation is fairly effective, seen from the observation sheet and questionnaire students. Almost all of the planning can be carried out properly in accordance with the expected phase. Time used in implementing learning activities using POE-based demonstration methods of proper accounting and in accordance with the planning. The average student responses indicate the student participation in learning activities amounted to 92%. This indicates that most of the activities involve students actively. ---------- Pembelajaran dengan menggunakan metode demonstrasi berbasis Predict- Observe- Explain (POE) pada materi pemanasan global menunjukkan hasil yang baik. Kemampuan siswa tentang prediksi, observasi, dan eksplanasi dapat dikembangkan dengan menggunakan metode ini. Level efektivitas kegiatan pembelajaran siswa sudah sangat baik pada tingkat efektivitas level 1. Pengembangan menuju level efektivitas 2 dapat dilakukan dengan pengembangan kemampuan prediksi dan eksplanasi. Indikator yang dicapai sesuai yang diharapkan hanya berjumlah 2 indikator dari 5 indikator yang ditetapkan. Peningkatan rata-rata pretest-posttest siswa menunjukkan kenaikan sebanyak 6,47 poin, meskipun indeks Gain yang diperoleh masih sebesar 0,3. Persentase keterlibatan siswa dalam kegiatan pembelajaran dengan metode demonstrasi berbasis POE mencapai rata-rata 92%. Hal ini berarti siswa melakukan kegiatan yang direncanakan dalam proses pembelajaran dengan baik. kemampuan siswa dalam hal observasi sangat terlihat dan sangat menonjol, disusul dengan kemampuan prediksi dan eksplanasi dengan persentasi berdasarkan lembar isian siswa sebesar 83,3 % untuk kemampuan observasi, 80% untuk kemampuan prediksi, dan 70% untuk kemampuan eksplanasi. Kesesuaian antara perencanaan dan pelaksanaan terbilang efektif, dilihat dari lembar observasi dan kuesioner siswa. Hampir semua perencanaan dapat dilaksanakan dengan baik sesuai dengan tahapan yang diharapkan. Waktu yang digunakan dalam melaksanakan kegiatan pembelajaran dengan menggunakan metode demonstrasi berbasis POE terhitung tepat dan sesuai dengan perencanaan. Rata-rata respon siswa yang menunjukkan partisipasi siswa dalam kegiatan pembelajaran adalah sebesar 92%. Hal ini menunjukkan bahwa sebagian besar kegiatan melibatkan siswa secara aktif.